Democracy goes to war : British military deployments under international law - White, N. D., 1961- (Oxford : Oxford University Press, 2009)
British troops are increasingly deployed around the world. This book considers the different constitutional frameworks that operate at national & international levels within which troop deployments are made by the British government, & assesses whether mechanisms of democratic accountability can contribute to upholding international law.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Military assistance, British -- Foreign countries; Military missions; International law; National security -- Law and legislation